Methodology of Teaching "Hellados" Story (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2023)
In this article, a number of studies on the teaching methodology of the story "Hellados", which is one of the examples of world literature, are analyzed. In this, the analysis of the work of art based on the cultural aspects of the nation forms the basis of the work, and the necessary theoretical conclusions are given.